2019
DOI: 10.1021/acschemneuro.8b00579
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of α-Synuclein Mutants on Lipid Binding and Aggregation Detected by Single Molecule Fluorescence Spectroscopy and ThT Fluorescence-Based Measurements

Abstract: Six α-synuclein (aSyn) point mutations are currently known to be associated with familial parkinsonism: A30P, E46K, H50Q, G51D, A53E, and A53T. We performed a comprehensive in vitro analysis to study the impact of all aSyn mutations on lipid binding and aggregation behavior. Markedly reduced lipid binding of A30P, moderately attenuated binding of G51D, and only very slightly reduced binding for the other mutants were observed. A30P was particularly prone to form metal ion induced oligomers, whereas A53T exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 61 publications
2
63
0
Order By: Relevance
“…Similarly, one would expect an increased BiFC signal when using proteins with disease-specific point mutations such as A53T, that promote a-syn aggregation. Although several a-syn PDassociated mutants have been shown to promote a-syn oligomerization and/or fibril formation in vitro (de Oliveira & Silva, 2019;Ruf et al, 2019), in cells (M. B. Fares et al, 2014;Khalaf et al, 2014;Lei, et al, 2019) and in vivo (Mbefo et al, 2015;Paumier et al, 2013), Lázaro et al reported identical Venus BiFC signals from WT a-syn and the PD-linked mutants A30P, E46K, H50Q, G51D and A53T (Lázaro et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, one would expect an increased BiFC signal when using proteins with disease-specific point mutations such as A53T, that promote a-syn aggregation. Although several a-syn PDassociated mutants have been shown to promote a-syn oligomerization and/or fibril formation in vitro (de Oliveira & Silva, 2019;Ruf et al, 2019), in cells (M. B. Fares et al, 2014;Khalaf et al, 2014;Lei, et al, 2019) and in vivo (Mbefo et al, 2015;Paumier et al, 2013), Lázaro et al reported identical Venus BiFC signals from WT a-syn and the PD-linked mutants A30P, E46K, H50Q, G51D and A53T (Lázaro et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that αSyn interacts with membrane lipid components, which could be targets for αSyn toxicity [4042]. In vitro studies showed that A30P and G51D mutations of αSyn had decreased lipid binding, whereas A53T and H50Q mutations did not differ from WT αSyn in their lipid binding [4346]. Therefore, a universal mechanism of enhanced toxicity that applies to all αSyn mutants still remains elusive, and each mutation may have different and multiple mechanisms for their toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Expression and purification were performed as previously described [19,20]. Briefly, the pET5α/αSynuclein (136 TAT) plasmid (wt‐plasmid by Philipp Kahle, LMU Munich; 136‐TAC/TAT‐mutation by Matthias Habeck) was transformed into BL21(DE3) Escherichia coli (New England Biolabs, Frankfurt am Main, Germany).…”
Section: Methodsmentioning
confidence: 99%